Alternative Asymptotic Tests of Significance and Related Aspects of 2SLS and 3SLS Estimated Parameters - Dhrymes, P. J. (Review of Economic Studies, 1969)
Journal Article Alternative Asymptotic Tests of Significance and Related Aspects of 2SLS and 3SLS Estimated Parameters Get access P. J. Dhrymes P. J. Dhrymes University of Pennsylvania Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 36, Issue 2, April 1969, Pages 213–226, https://doi.org/10.2307/2296838 Published: 01 April 1969 Article history Received: 03 October 1967 Revision received: 08 August 1968 Published: 01 April 1969